Narratives reflecting the lived experiences of people with brain disorders: common psychosocial difficulties and determinants. - Sally Hartley (Public Library of Science (PLoS), 2014)
Background People with brain disorders - defined as both, mental disorders and neurological disorders experience a wide range of psychosocial difficulties (PSDs) (e.g., concentrating, maintaining energy levels, and maintaining relationships). Research evidence is required to show that these PSDs are common across brain disorders. Objectives To explore and gain deeper understanding of the experiences of people with seven brain disorders (alcohol dependency, depression, epilepsy, multiple sclerosis, Parkinson's disease, schizophrenia, stroke). It examines the common PSDs and their influencing factors. Methods Seventy seven qualitative studies identified in a systematic literature review and qualitative data derived from six focus groups are used to generate first-person narratives representing seven brain disorders. A theory-driven thematic analysis of these narratives identifies the PSDs and their influencing factors for comparison between the seven disorders. Results First-person narratives illustrate realities for people with brain disorders facilitating a deeper understanding of their every-day life experiences. Thematic analysis serves to highlight the commonalities, both of PSDs, such as loneliness, anger, uncertainty about the future and problems with work activities, and their determinants, such as work opportunities, trusting relationships and access to self-help groups. Conclusions The strength of the methodology and the narratives is that they provide the opportunity for the reader to empathise with people with brain disorders and facilitate deeper levels of understanding of the complexity of the relationship of PSDs, determinants and facilitators. The latter reflect positive aspects of the lives of people with brain disorders. The result that many PSDs and their influencing factors are common to people with different brain disorders opens up the door to the possibility of using cross-cutting interventions involving different sectors. This strengthens the message that 'a great deal can be done' to improve the lived experience of persons with brain disorders when medical interventions are exhausted.